Pertanggungjawaban Hukum Rumah Sakit Terkait Kebocoran Data Pribadi Pasien Berdasarkan Peraturan Perundang-Undangan - Erwin Tumpal Ferdinand Tampubolon; Andika Persada Putera; M. Khoirul Huda (Syntax Idea)
The issue of personal data leaks in Indonesia, including in the healthcare sector, is increasingly alarming. Hospitals, as corporations, bear significant responsibility in safeguarding the personal data of patients and the potential legal consequences arising from any data breaches. This thesis aims to elucidate the accountability of hospitals concerning the leakage of patients' personal data based on legal regulations. In order to guarantee the protection of patients' personal information in hospitals, the government must provide an appropriate legislative framework that complies with current laws and regulations. Consequently, patients can have legal certainty and trust that their personal data or health information will not be compromised during medical procedures at hospitals. As corporations, hospitals are unable to avoid their legal obligations. This duty includes all civil, criminal, and administrative legal responsibilities pertaining to the disclosure of patient information. By understanding and implementing these provisions, hospitals can effectively safeguard the security of patient's personal data and avoid adverse legal consequences.